The mediating role of relatedness need satisfaction in the relationship between charitable behavior and well‐being: Empirical evidence from China. (3rd August 2016) - Jiang, Jiang; Zeng, Taoran; Zhang, Chong; Wang, Rong
Abstract : Based on self‐determination theory, the current research aimed to explore the potential mediating effect of relatedness need satisfaction on the relationship between charitable behavior and well‐being in the Chinese context. Employing a cross‐sectional design, participants reported data on the aforementioned variables in Study 1. The results indicated that relatedness need satisfaction mediated the positive relationship between charitable behavior and hedonic well‐being and that between charitable behavior and eudaimonic well‐being. Subsequently, a field experiment was conducted in Study 2. Participants rated their levels of relatedness need satisfaction and well‐being after charitable donation behaviors were primed. We again observed consistent results. Specifically, charitable behavior was positively associated with both hedonic and eudaimonic well‐being, and these relationships were mediated by relatedness need satisfaction. The above findings help to clarify the association between charitable behavior and people's subjective feelings (i.e., well‐being), and they deepen our understanding of the underlying mechanism from the perspective of psychological needs satisfaction.